Clinical Aspects of Patients with Acne Vulgaris in Basrah city - Abed Radhi, Ali; S Issa, Sajjad (International Journal of Psychosocial Rehabilitation, 2020)
Acne vulgaris is chronic inflammatory disease of pilosebaceous unit. It is a common problem affecting significant proportion of young people. The study aims to find out any association between the clinical aspects of disease and the socio-demographic characteristics of the studied sample. In the present study, patients (12-29year age) showing acne vulgaris (n=150 content 96 females and 54 males) was enrolled. They were assessed by direct interview and examination for their acne, scarring and any hyper androgenic evidence, according to Allen and smith grading system. Premenstrual flare (40.6%) was notice and had association with the grading (P=0.001).Sweating and hot weather were observed in 68.0% of cases. Stress and high fatty food intake were 64.0% and 52%, respectively. Digging or squeezing habits was significantly associated with the grading of acne (P=0.012 and P=0.004 respectively). Greasy skin showed maximum occurrence (69.3%) of acne. Scars (pitting hyper pigmented scars) were noticed in 34% patients. The most common effect of acne and scarring on the psyche of patients was a mild psychological disturbance or mild dysmorphophobia (38%). High fatty diets intake and digging or squeezing habits can be appeared as a risk factors for the severity of acne. Although clinically the mild form of acne was commonly reported, it was associated with significant physical scars and psychological discomfort.